2021
DOI: 10.1097/iop.0000000000002013
|View full text |Cite
|
Sign up to set email alerts
|

Gender Authorship Trends in the Ophthalmic Plastic and Reconstructive Surgery Literature

Abstract: Purpose: Despite increasing numbers of women oculoplastic surgeons, they remain underrepresented within the subspecialty. The purpose of this study was to analyze trends in gender authorship within the field of ophthalmic plastic and reconstructive surgery. Methods: This retrospective observational study sampled articles published in Ophthalmic Plastic and Reconstructive Surgery (OPRS) and Orbit during the years 1985, 1995, 2005, 2015, and 2020. Data reviewed included article type, total number of authors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Interestingly, our study further revealed that female PDs had significantly higher five-year h-indexes compared to their male counterparts, suggesting a trend toward greater research productivity among the former group in more recent years. This is consistent with broader findings from other investigations that have noted a greater number of female authors among OPRS-specific journals and presenters at ASOPRS meetings [12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, our study further revealed that female PDs had significantly higher five-year h-indexes compared to their male counterparts, suggesting a trend toward greater research productivity among the former group in more recent years. This is consistent with broader findings from other investigations that have noted a greater number of female authors among OPRS-specific journals and presenters at ASOPRS meetings [12,13].…”
Section: Discussionsupporting
confidence: 92%
“…Elkbuli et al reported that among medical school deans, men held significantly higher lifetime peer-reviewed publications and h-indices compared to women. 11 The lack of representation of women within 16 Aslan et al 17 Silvestre et al 18 Sela et al 19 Xiao et al 20 Brown et al 21 Pastor-Cabeza et al 22 Hiller et al 23 Farhan et al 24 Arrighi-Allisan et al 25 Gervasio et al 26 surgical research found by this review may impact advancement of women surgeons to positions of leadership, further highlighting the interplay between research productivity and academic leadership. 12,[30][31][32] Interestingly, one study found that women were significantly less likely to hold senior leadership positions in academic medicine than men after controlling for research productivity, indicating that additional factors may play a role in the underrepresentation of women within academic surgery.…”
Section: Discussionmentioning
confidence: 93%
“…A total of 15 studies met our eligibility criteria and were included in the meta-analysis (eTable 1). 1,12,[15][16][17][18][19][20][21][22][23][24][25][26][27] Three studies investigated orthopedic surgery research, 15,21,23 three studies investigated neurosurgery research, 17,22,24 two studies investigated plastic surgery research, 18,26 and two studies investigated research from multiple surgical specialties. 16,20 The remaining five studies investigated research from surgical subspecialties and are reported in eTable 1.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations